TINGKAT BURNOUT CAREGIVER KLIEN SKIZOFRENIA DI DESA KERSAMANAH KABUPATEN GARUT - Yulianti Yulianti; Aulia Iskandarsyah; Imas Rafiyah (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2018)
The prevalence of burnout in caregiver clients schizophrenia shows a fairly high rate compared with other chronic diseases. Burnout is a psychological tension that is specifically related to chronic stress experienced by individuals from day to day and is characterized by a state of physical, mental, and emotional exhaustion. This condition can cause the caregiver to experience depression or mental disorder. The purpose of this research is to indicate the burnout caregiver level of schizophrenia clients. This research is a descriptive research conducted in the Village Kersamanah, Garut Regency. The caregiver burnout rate is measured using Maslach Burnout Inventory-Human Services Survey (MBI-HSS). The results show that the burnout caregiver level of schizophrenic clients most of caregiver were at high burnout rate–sixty three percent (63%). The results of this study are expected to shade a light of knowledge in the mental treatment nursing, especially to overcome psychosocial problems, particularly in burnout that occurs in caregiver schizophrenia.Keywords: burnout, caregiver, schizophrenia